Small-Animal PET of Steroid Hormone Receptors Predicts Tumor Response to Endocrine Therapy Using a Preclinical Model of Breast Cancer - Amy M. Fowler; Szeman Ruby Chan; Terry L. Sharp; Nicole Fettig; Dong Zhou; Carmen S. Dence; Kathryn E. Carlson; M. Jeyakumar; John A. Katzenellenbogen; Robert D. Schreiber; Michael J. Welch (2012)
Estrogen receptor-α (ERα) and progesterone receptor (PR) are expressed in most human breast cancers and are important predictive factors for directing therapy. Because of de novo and acquired resistance to endocrine therapy, there remains a need to identify which ERα-positive (ERα+)/PR-positive (PR+) tumors are most likely to respond. The purpose of this study was to use estrogen- and progestin-based radiopharmaceuticals to image ERα and PR in mouse mammary tumors at baseline and after hormonal therapy and to determine whether changes in these imaging biomarkers can serve as an early predictive indicator of therapeutic response. Methods: Mammary adenocarcinomas that spontaneously develop in aged female mice deficient in signal transducer and activator of transcription-1 (STAT1) were used. Imaging of ERα and PR in primary tumor–bearing mice and mice implanted with mammary cell lines (SSM1, SSM2, and SSM3) derived from primary STAT1-deficient (STAT1−/−) tumors was performed. Hormonal treatments consisted of estradiol, an ER agonist; letrozole, an aromatase inhibitor; and fulvestrant, a pure ER antagonist. Small-animal PET/CT was performed using 18F-fluoroestradiol (18F-FES) for ER, 18F-fluoro furanyl norprogesterone (18F-FFNP) for PR, and 18F-FDG for glucose uptake. Tracer uptake in the tumor was quantified and compared with receptor concentration determined by in vitro assays of resected tumors. Results: Primary STAT1−/− mammary tumors and implanted SSM2 and SSM3 tumors showed high 18F-FES and 18F-FFNP uptake and were confirmed to be ERα+/PR+. Classic estrogen-induced regulation of the progesterone receptor gene was demonstrated by increased 18F-FFNP uptake of estradiol-treated SSM3 tumors. Treatment with fulvestrant decreased 18F-FFNP, 18F-FES, and 18F-FDG uptake and inhibited growth of SSM3 tumors but decreased only 18F-FES uptake in SSM2 tumors, with no effect on growth, despite both tumors being ERα+/PR+. Decreased 18F-FFNP uptake by SSM3 tumors occurred early after initiation of treatment, before measurable tumor growth inhibition. Conclusion: Using small-animal PET, a profile was identified that distinguished fulvestrant-sensitive from fulvestrant-resistant ERα+/PR+ tumors before changes in tumor size. This work demonstrates that imaging baseline tumoral 18F-FES uptake and initial changes in 18F-FFNP uptake in a noninvasive manner is a potentially useful strategy to identify responders and nonresponders to endocrine therapy at an early stage.